Wideband and high gain dielectric resonator antenna for 5G applications - Irfan Ali; Mohd Haizal Jamaluddin; M. R. Kamarudin; Abinash Gaya; R. Selvaraju (Institute of Advanced Engineering and Science, 2019)
In this paper, wideband high gain dielectric resonator antenna for 5G applications is presented. Higher order mode is exploited to enhance the antenna gain, while the array of symmetrical cylindrical shaped holes drilled in the DRA to improves the bandwidth by reducing the quality factor. The proposed DRA is designed using dielectric material with relative permittivity of 10 and loss tangent of 0. 002.The Rogers RT/Droid 5880 has been selected as substrate with relative permittivity of 2.2, loss tangent of 0.0009- and 0.254-mm thickness. The simulated results show that, the proposed geometry has achieved a wide impedance bandwidth of 17.3% (23.8-28.3GHz=4.5 GHz) for S11<-10 dB, and a maximum gain of about 9.3 dBi with radiation efficiency of 96% at design frequency of 26 GHz. The DRA is feed by microstrip transmission line with slot aperture. The reflection coefficient, the radiation pattern, and the antenna gain are studied by full-wave EM simulator CST Microwave Studio. The proposed antenna can be used for the 5G communication applications such as device to device communication (D2D).